If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( x )
5*x+15 = 0
x+3 = 0
5*x+15 = 0
5*x+15 = 0
5*x+15 = 0 // - 15
5*x = -15 // : 5
x = -15/5
x = -3
x+3 = 0
x+3 = 0
x+3 = 0 // - 3
x = -3
x in (-oo:-3) U (-3:+oo)
4/(x+3)-(5/4) = 7/(5*x+15) // - 7/(5*x+15)
4/(x+3)-(7/(5*x+15))-(5/4) = 0
4/(x+3)-7*(5*x+15)^-1-5/4 = 0
4/(x+3)-7/(5*x+15)-5/4 = 0
(4^2*(5*x+15))/(4*(x+3)*(5*x+15))+(-7*4*(x+3))/(4*(x+3)*(5*x+15))+(-5*(x+3)*(5*x+15))/(4*(x+3)*(5*x+15)) = 0
4^2*(5*x+15)-7*4*(x+3)-5*(x+3)*(5*x+15) = 0
52*x-25*x^2-150*x-225+156 = 0
-25*x^2-98*x-69 = 0
-25*x^2-98*x-69 = 0
-1*(25*x^2+98*x+69) = 0
25*x^2+98*x+69 = 0
DELTA = 98^2-(4*25*69)
DELTA = 2704
DELTA > 0
x = (2704^(1/2)-98)/(2*25) or x = (-2704^(1/2)-98)/(2*25)
x = -23/25 or x = -3
-1*(x+3)*(x+23/25) = 0
(-1*(x+3)*(x+23/25))/(4*(x+3)*(5*x+15)) = 0
(-1*(x+3)*(x+23/25))/(4*(x+3)*(5*x+15)) = 0 // * 4*(x+3)*(5*x+15)
-1*(x+3)*(x+23/25) = 0
( x+23/25 )
x+23/25 = 0 // - 23/25
x = -23/25
( x+3 )
x+3 = 0 // - 3
x = -3
x in { -3}
x = -23/25
| 2+8x=51-3x | | 5x+35=15x+4 | | 4x=18-5x | | x+y/z-a=b | | 6.5/3x+5=24.5 | | (4-3i)(1-I)-(2-I)(2+I)= | | 6.5/3x+5=11.5 | | 2/(-4)^-3 | | 12x+16=5x+198 | | -5n-2= | | 6x+10+6x=154 | | 4x=24+2x | | -2n+6= | | p-9=7p+9 | | 8/(a)-(5/8)=(-4/3)-6/(8a) | | (8/a)-(5/8)=(-4/3)-(6/8a) | | 10(x+3)+-(-9x-4)=x+-5+3 | | 8/a-5/8=-4/3-6/8a | | 4(x-2)+3x=6 | | 17=-2m+5 | | -7(1-6m)=-133 | | 2-4x=-30 | | 225x^2-16=0 | | 4(x-1)+x=6 | | 10x+5y=72 | | 7/(s-8)=-3/(5s+3) | | 4(x-3)+2x=24 | | -81=3(-6-3x) | | -2+2x+4x=64 | | (7/s-8)=-3/5s+3 | | 5n-3= | | -184=8(-3-4n) |